Práticas corporais de aventura na Educação Física escolar: desafios e possibilidades lúdicas e educativas nos anos iniciais do ensino fundamental - Fornazier, Gisele Pereira dos Santos (2024)
The present investigation focuses on the teaching of Adventure Physical Practices (APPs) in Physical Education classes in the early years of elementary school. The research problem was to identify how APPs in school Physical Education can be addressed using games and play as pedagogical tools. The main objective was to plan and implement a systematic didacticpedagogical sequence for teaching APPs in the early years of elementary school, using games and play in Physical Education classes, and to analyze their playful and educational potential. The research follows a qualitative approach, and the methodology is based on the principles of action research, involving students from a public school in Goiânia, Goiás. The pedagogical proposal was carried out during Physical Education classes over the course of 12 interventions with a 1st-grade class consisting of 21 students from the afternoon shift, between October and December 2023. Research instruments included a field journal, discussion circles, photo records, voice recordings, and children's drawings produced at the end of the pedagogical sequence. We identified some challenges, such as the lack of specific materials for the interventions and a lack of support during the implementation of the classes, which were limiting factors but were addressed with possible adaptations. In our experiential narratives, we found that the APP proposal outlined in the Goiás Curriculum Document (DCGO) was feasible for the class. Based on the research on APPs, it was concluded that the pedagogical proposal experienced by the children significantly contributed to expanding their knowledge, learning, and the development and progression of motor, cognitive, affective, and social aspects.